Growth inhibition of Fusarium verticillioides (Sacc.) Nirenberg by isolates of Trichoderma pseudokoningii strains from maize plant parts and its rhizosphere - Sobowale, A.A.; Cardwell, K.; Odebode, A.; Bandyopadhyay, Ranajit; Jonathan, S. (2005)
Ability of five strains of Trichoderma pseudokoningii (antagonists) to sup-press radial growth of Fusarium verticillioides (Sacc.) Nirenberg (=Fusarium moniliformeSheldon) was examined in vitro. These were T. pseudokoningiistrain1 (IMI 380933), strain2 (IMI 380937), strain3 (IMI 3809 39), strain4 (IMI 380940) and strain5 (IMI 380941). Each strain was paired with pathogen by inoculating at opposite ends of 9 cm petri plates using three pairing methods. Gradings were assigned to varied growth inhibition of pathogen by antagonists and analysed using GLM procedure (SAS). Growth suppression of F. verticillioidesby all strains of T. Pseudokoningii was significantly different (R2=0.98, p=0.05) from control in all pairing methods. It differed significantly (p>0.0003) among the strains in all pairing methods. Growth suppression also differed significantly among (p>0.0001) and within (p>0.018) pairingmethods. Growth suppression was best when antagonists were inoculated before pathogen. Suppression mechanisms include mycoparasitism and competition for space and nutrients. T. pseudokoningiistrains 3 and 4 had the best (p=0.05) growth suppression of F. verticillioides and could be used as biocontrol agents for endophytic F. verticillioidesin maize plant. This experiment was conducted in the search for resident microorganisms that might be capable of checking F. verticillioides within maize plant by competitive exclusion in subsequent experiments.